Analisis Prosedur Pemberian Kredit Usaha Rakyat dan Penanganan Kredit Macet Pada PT. Bank Rakyat Indonesia Unit Diponegoro Soe - Rufina Seno Saba; Apriana H.J Fanggidae; Maria Prudensiana Leda Muga (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research is motivated by the observation that in providing credit, good credit provision procedures must be considered so that it can reduce the impact of the risk of non-performing loans and efforts are also needed to handle cases of increasing non-performing loans. This study aims to (1) analyze the procedure for providing People's Business Credit (KUR) and (2) handling non-performing loans at PT. BRI Unit Diponegoro. People's Business Credit is one of the government programs that aims to encourage the development of micro, small and medium enterprises (UMKM) in Indonesia. The procedure for providing KUR at PT. BRI Unit Diponegoro involves a series of stages, starting from credit applications, field surveys and verifications, credit analysis, credit granting decisions and credit disbursement. This study also examines the mechanism for handling non-performing loans which includes identifying the causes of late payments, credit restructuring, revitalization of mantri and summons to the court. The method used in this study is a case study with a qualitative approach, where data is collected through interviews and analysis of related documents. The results of the study indicate that although the KUR provision procedure is in accordance with applicable provisions, the biggest challenge lies in the loan fund manager, in this case the customer. Customers are unable to manage loan funds properly and are used for needs outside of business interests, of course this requires a more effective and efficient handling strategy. Proper handling of bad debts can help minimize losses and increase the sustainability of the KUR program, as well as support the development of MSMEs in the region.